Positive affect moderates the effect of negative affect on cardiovascular disease-related hospitalizations and all-cause mortality after cardiac rehabilitation. (29th August 2020) - Meyer, Fiorenza Angela; von Känel, Roland; Saner, Hugo; Schmid, Jean-Paul; Stauber, Stefanie
Abstract: Background: Little is known as to whether negative emotions adversely impact the prognosis of patients who undergo cardiac rehabilitation. We prospectively investigated the predictive value of state negative affect (NA) assessed at discharge from cardiac rehabilitation for prognosis and the moderating role of positive affect (PA) on the effect of NA on outcomes. Methods: A total of 564 cardiac patients (62.49 ± 11.51) completed a comprehensive three-month outpatient cardiac rehabilitation program, filling in the Global Mood Scale (GMS) at discharge. The combined endpoint was cardiovascular disease (CVD)-related hospitalizations plus all-cause mortality at follow-up. Cox regression models estimated the predictive value of NA, as well as the moderating influence of PA on outcomes. Survival models were adjusted for sociodemographic factors, traditional cardiovascular risk factors, and severity of disease. Results: During a mean follow-up period of 3.4 years, 71 patients were hospitalized for a CVD-related event and 15 patients died. NA score (range 0–20) was a significant and independent predictor (hazard ratio (HR) 1.091, 95% confidence interval (CI) 1.012–1.175; p = 0.023) with a three-point higher level in NA increasing the relative risk by 9.1%. Furthermore, PA interacted significantly with NA ( p < 0.001). The relative risk of poor prognosis with NA was increased in patients with low PA ( p = 0.012) but remained unchanged in combination with high PA ( p = 0.12). Conclusion: The combination of NA with low PA was particularly predictive of poor prognosis. Whether reduction of NA and increase of PA, particularly in those with high NA, improves outcome needs to be tested.